1993
DOI: 10.3109/10428199309148542
|View full text |Cite
|
Sign up to set email alerts
|

Six Colombian Patients with Adult T–Cell Leukemia/Lymphoma

Abstract: Six Colombian patients with adult T-cell leukemia/lymphoma (ATL) are presented. The clinical and hematological features, the familial clusters of human T lymphotropic virus type 1 (HTLV-I) carriers and the prognoses of the Colombian ATL patients were similar to those previously reported for Japanese ATL patients. The only difference was the mean age of onset, which was more than 20 years younger than in Japanese patients. Three patients with ATL were suffering from strongyloidiasis. In one patient it was sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
1
8
0
3
Order By: Relevance
“…Polyclonal proliferation and increased numbers of HTLV-1-infected cells would favor genetic changes, the result being accelerated leukemogenesis. This notion is in line with clinical observations that the average age at the onset of ATL in Colombian, Caribbean and African patients is younger than in the Japanese Blank et al, 1993), and in a younger onset of ATL patients with strongyloidiasis in Martinique (French West India) (Plumelle et al, 1993). It was also reported that ATL developed after 7 years of observation in an asymptomatic HTLV-1 carrier with strongyloidiasis, who was born in Martinique (Patey et al, 1992).…”
Section: Discussionsupporting
confidence: 74%
“…Polyclonal proliferation and increased numbers of HTLV-1-infected cells would favor genetic changes, the result being accelerated leukemogenesis. This notion is in line with clinical observations that the average age at the onset of ATL in Colombian, Caribbean and African patients is younger than in the Japanese Blank et al, 1993), and in a younger onset of ATL patients with strongyloidiasis in Martinique (French West India) (Plumelle et al, 1993). It was also reported that ATL developed after 7 years of observation in an asymptomatic HTLV-1 carrier with strongyloidiasis, who was born in Martinique (Patey et al, 1992).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, there is evidence that HTLV-1 can influence the outcome and severity of other infections such as tuberculosis (Verdonck et al, 2007a), HIV (Brites et al, 2001; Silva et al, 2009), and hepatitis C (Castro and Roger, 2016). Although none of the records suggested the role of co-infections in explaining family aggregation, they did report families in which co-infections (i.e., strongyloidiasis and infective dermatitis) were present (Blank et al, 1993; Wilks et al, 1993; LaGrenade et al, 1996; Gonçalves et al, 1999; Araújo et al, 2002; Mahé et al, 2004; Primo et al, 2005; Nobre et al, 2006; Suite et al, 2009; Alvarez et al, 2011; da Silva et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Seis tinham idade igual ou inferior a 10 anos na época do diagnóstico 31,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] .…”
Section: Leucemia/linfoma De Células T Do Adultounclassified